1989
DOI: 10.3758/bf03334603
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific preferences in prairie voles, Microtus ochrogaster, and meadow voles, M. pennsylvanicus

Abstract: Interactions between congeneric species in sympatry offer opportunities to study mating preferences for conspecifics, preferences that maintain premating reproductive isolation between species. Sixteen males and 16 females of two sympatric species, prairie voles (Microtus ochrogaster) and meadow voles (M pennsylvanicus), were tested for conspecific as opposed to heterospecific preferences in an automated preference apparatus. The results indicated that male prairie and meadow voles displayed preferences for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Consequently, both LPS-and saline-injected males were not familiar partners in the present study; thus, to avoid the confound of familiarity among prairie voles, we used only sexually naive females in the present study. Previous data suggested that female prairie voles exhibit distinct preferences for conspecific males regardless of estrous stage (Pierce, Ferguson, & Dewsbury, 1989). In contrast, female meadow voles in diestrus do not appear to distinguish between males during partner preference tests, suggesting that the observed species difference in partner preference behavior in the present study may reflect species differences in female reproductive status and social organization.…”
Section: Discussioncontrasting
confidence: 60%
“…Consequently, both LPS-and saline-injected males were not familiar partners in the present study; thus, to avoid the confound of familiarity among prairie voles, we used only sexually naive females in the present study. Previous data suggested that female prairie voles exhibit distinct preferences for conspecific males regardless of estrous stage (Pierce, Ferguson, & Dewsbury, 1989). In contrast, female meadow voles in diestrus do not appear to distinguish between males during partner preference tests, suggesting that the observed species difference in partner preference behavior in the present study may reflect species differences in female reproductive status and social organization.…”
Section: Discussioncontrasting
confidence: 60%
“…Meadow voles have been shown to display avoidance of sibling inbreeding (Bollinger, Harper, Kramer, & Barrett, 1991). Male meadow voles prefer to associate with conspecific females, rather than with female prairie voles, but only when the females are in estrus (Pierce, Ferguson, & Dewsbury, 1989). Conspecific preferences appear rather unaffected by cross-fostering (McGuire & Novak, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the longer period of estrus induction may afford both the male and female greater opportunity for mate evaluation, thought to be important in monogamous species. Monogamous vole species generally display mate choice more readily than polygamous species (Pierce, 1989; Pierce & Dewsbury, 1991; Pierce, Ferguson, & Dewsbury, 1989; Shapiro, Austin, Ward, & Dewsbury, 1986; Shapiro & Dewsbury, 1986).…”
Section: Discussionmentioning
confidence: 99%